Rachunek kosztów działań w symulatorze dydaktycznym przedsiębiorstwa produkcyjnego - Bojnowska, Agnieszka; Josek, Wojciech; Kuchta, Dorota (Use of Activity Based Costing in Production Company Educational Simulator, 2007)
The main purpose of the article is to present an educational process concerning the implementation of Activity Based Costing (ABC) method in a production company with the usage of computer simulator called Ek_AN. The idea behind is to involve participants (students) to work on the model of cost allocation (using ABC) for virtual production company, during which they get acknowledged with the scope of information they can obtain, using ABC, with comparison to results from traditional cost settlement methods. Didactic process which includes personal students' engagement and active participation in decision making (cost identification and settlement), as the authors of the article show, results in better understanding, remembering and retaining the nature of the ABC method.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 38-44